Survey of media forms and information flow models in microsystems companies - Durugbo, Christopher; Tiwari, Ashutosh; Alcock, Jeffrey R. (Cranfield University, 2010)
The paper presents the findings of a survey of 40 microsystems companies that was carried out to determine the use and the purpose of use of media forms and information flow models within these companies. These companies as "product-service systems' delivered integrated products and services to realise customer solutions. Data collection was carried out by means of an online survey over 3 months. The survey revealed that 42.5% of respondents made use of data flow diagrams and 10% made use of design structure matrices. The survey also suggests that a majority of companies (75%) made use of textual and diagrammatic media forms for communication, analysis, documentation and representation during design and development processes. The paper also discusses the implications of the survey findings to product-service systems.